2014
DOI: 10.1186/1472-6831-14-143
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral candidiasis and low CD4+ count among HIV positive patients in Hoima Regional Referral Hospital

Abstract: BackgroundThe aim of this study was to determine the prevalence of Human Immune Virus (HIV) related oral lesions and their association with Cluster of Differentiation 4 (CD4+) count among treatment naïve HIV positive patients.MethodsThis was a descriptive and analytical cross sectional study. Participants were 346 treatment naïve HIV positive adult patients. These were consecutively recruited from Hoima Regional Referral hospital between March and April 2012. Data collection involved interviews, oral examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 18 publications
2
24
1
Order By: Relevance
“…24 Nanteza et al, in 2014, with their descriptive and analytical cross-sectional study in Uganda also showed there was a significant association between oral candidiasis and CD4 counts less than 350 cells/ μL (P<0.001; OR=2.69; 95% CI: 1.608-4.502). 37 A study in Brazil also concluded CD4 less than 350 cell/μL had a higher risk for developing OC compared more than 500 (p<0.001; OR=3.82; 95% CI: 2.16-6.77). 30 Takahashi et al, in 2015, reported the significant association between CD4 cell counts less than 100/µL with Candidiasis (p< 0.001).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…24 Nanteza et al, in 2014, with their descriptive and analytical cross-sectional study in Uganda also showed there was a significant association between oral candidiasis and CD4 counts less than 350 cells/ μL (P<0.001; OR=2.69; 95% CI: 1.608-4.502). 37 A study in Brazil also concluded CD4 less than 350 cell/μL had a higher risk for developing OC compared more than 500 (p<0.001; OR=3.82; 95% CI: 2.16-6.77). 30 Takahashi et al, in 2015, reported the significant association between CD4 cell counts less than 100/µL with Candidiasis (p< 0.001).…”
Section: Discussionmentioning
confidence: 96%
“…41 Nanteza et al, in 2014, showed clinical WHO stage 3 had three times higher to develop OC compared to stage 1 (p=0.025; OR=3.803; 95% CI: 1.182-12.240). 37 Putranti et al, in 2018, also showed oral candidiasis mostly appeared in clinical stage 4. A study held in India revealed an oral lesion was considered to be marker of progression of HIV into the final clinical stage of AIDS.…”
Section: Discussionmentioning
confidence: 96%
“…albicans lives commensally in the gut, oral pharyngeal, genito-urinary tract and skin [ 2 ]. However, pathogenicity and subsequent candidiasis can occur under immunocompromised conditions [ 3 , 4 ]. For instance, the incidence of at least one episode of oral candidiasis in HIV patients is estimated to be 80–95% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…National + international Kreusch and Karstaedt, 2013 [39] Tshukutsoane and Scribante, 2008 [40] Govender et al, 2016 [37] Candida peritonitis Post-surgical Candida peritonitis is half as common as ICU-related candidemia; PD patients assumed to have 1.7 episodes of peritonitis per year, with 3.8% due to Candida National + international Montravers et al, 2011 [41] Okpechi et al, 2012 [42] Isla et al, 2014 [43] Oral candidiasis Among adults, 38% of PLWH with CD4+ <350 cells/µL; for children living with HIV, oral candidiasis assumed to affect 37% not on ART and 5% on ART National + regional Arendorf et al, 1998 [44] Nanteza et al, 2014 [45] Meless et al, 2014 [46] Rwenyonyi et al, 2011 [48] Oesophageal candidiasis 20% of PLWH with CD4 <200 cells/µL International Smith and Orholm, 1990 [49]…”
Section: Safsmentioning
confidence: 99%
“…[42,43] Oral candidiasis was assumed to affect 38% of adult PLWH who had CD4+ counts <350 cells/µL; this estimate was based on a large SA study in the pre-ART era that reported oral candidiasis among 38% of HIV-infected patients, [44] in addition to a study from Uganda that suggested that this opportunistic infection is significantly more likely below this CD4+ threshold. [45] Oral candidiasis was assumed to affect 5% of children living with HIV on ART [46] and 37% of children living with HIV not taking ART, [47,48] based on data from elsewhere in sub-Saharan Africa. Oesophageal candidiasis was assumed to affect 20% of adult PLWH who had CD4+ counts <200 cells/µL, based on a study from Denmark of patients with AIDS; [49] estimates were not attempted for this disease among children.…”
Section: Researchmentioning
confidence: 99%